Evaluation of FD2 (Frisby Davis distance) stereotest in surgical management of intermittent exotropia. Issue 10 (31st July 2013) - Singh, Abhishek; Sharma, Pradeep; Singh, Digvijay; Saxena, Rohit; Sharma, Anudeepa; Menon, Vimla
Abstract : Aim: To evaluate Frisby Davis distance (FD2) stereotest for determining the timing of surgical intervention in intermittent exotropia (X(T)). Methods: A prospective case–control study was conducted including 30 patients with X(T) and 30 age-matched controls. Stereoacuity was measured preoperatively and 3 months postoperatively using FD2 for distance and TNO and Randot for near. Results: Preoperative distance stereoacuity was 43.83±35.51 arcsec (median 30 arcsec; range 10–120) which improved postoperatively to 27±33.74 arcsec (median 15 arcsec; range 5–120) (p=0.001). Cases with FD2 stereoacuity worse than 70 arcsec did not show significant improvement. Mean preoperative near stereoacuity by TNO was 94.00±79.48 arcsec (median 60 arcsec) and Randot was 50.33±39.23 arcsec (median 30 arcsec) which improved to 80.00±80.08 arcsec (median 60 arcsec) and 34.17±57.00 arcsec (median 20 arcsec), respectively, after surgery (both p=0.001). The controls had a mean distance stereoacuity of 14.66±4.13 arcsec (median 15 arcsec; range 5–20) and near stereoacuity of 63.00±21.35 arcsec (median 60 arcsec (TNO)) and 23.66±5.07 arcsec (median 20 arcsec (Randot)). There was a significant correlation between FD2 and Randot in the cases but not in controls (p=0.005), however no correlation was found between TNO and FD2. Conclusions: Distance stereoacuity is reduced in X(T) to a greater extent than the near stereoacuity and both improve after surgery. FD2 is useful for deciding timing of surgery and a stereoacuity worse than 20 arcsec is an indication for surgical intervention. A preoperative distance stereoacuity which is worse than 70 arcsec implies a poor prognosis for stereoacuity improvement after surgery.